Gravity-based tools for assessing the impact of tariff changes - Arevik Gnutzmann-Mkrtchyan; Jules Hugot (Asian Development Bank (ADB), 2022)
This paper presents two empirical tools to quantify the impacts of tariff changes on bilateral trade and welfare. Both tools are rooted in the structural gravity literature. The first tool estimates the impact of tariff changes on bilateral trade for 5,020 products in a partial equilibrium framework. The second tool quantifies the impact on bilateral aggregate trade in a general equilibrium setup, allowing estimates of trade reallocation and welfare changes. These tools are used to estimate the impact of tariff changes affecting Armenia, including (i) the alignment with the external tariff of the Eurasian Economic Union, (ii) free trade agreements between the Eurasian Economic Union, and other economies-Iran and the People's Republic of China, and (iii) the loss of beneficiary status for the Generalised Scheme of Preferences of the European Union.
Keywords: F13; F14; F15; F17; 330; gravity; Eurasian Economic Union; free trade agreements; generalised scheme of preferences; Armenia